THE IMPACT OF IMPROVING ELECTRONIC HEALTH LITERACY SPECIFICALLY BY IMPLEMENTING E-PATIENT PROGRAMS IN THE INTERNAL MEDICINE AND SURGERY CLINICS TO DIMINISH WAITING TIMES AT WEST SULAWESI PROVINCIAL HOSPITAL - A. Erieka Novianti1, Atjo Wahyu 2, Ridwan Amiruddin3, Fridawaty Rifai4, Sukri Palutturi5, Djazuli Chalidyanto6, M. Alimin Maidin7, Sudirman Nasir8 (Chelonian Research Foundation, 2023)
Introduction: Associated with quality management, the aspect of long waiting time for patients to get health services is one of the important things and greatly determines the quality of health services provided by a health service unit, as well as reflecting how hospitals process service components that are tailored to patient situations and expectations. This study aims to analyze the effect of using e-patients through electronic health literacy on reducing waiting time in internal medicine and surgery clinics at West Sulawesi Provincial Hospital. Research Methodology: This study used quantitative methods with the design of the Experimental Quasy study. The informants in the study amounted to 180 people in the intervention group and 180 people in the control group. Data analysis using Wilcoxon, Mann Whitney, Hoteling T2, and Manova tests. Research Results: The results showed significant differences in the variables of ability to process information, involvement in self-health, ability to actively engage with health services, safe and controlled, motivation to engage with digital services, access to digital services, and digital services that are in accordance with needs with a value of p < 0.05. Keywords: Electronic Health Literacy, Waiting Time, e-Patient.